Numerical simulation of vertical annular andchurn air-water two-phase flows - Freitas, Larissa Steiger de (2021)
Two-phase flows have several applications in areas of engineering interest. They appear indistillation towers in the chemical industry, in refrigeration equipment in the thermal and nuclearpower generation industry, and in the oil industry. This work presents three-dimensional andtransient investigations on the annular and churn liquid-gas flow patterns, and the transitionbetween them. The continuity and momentum equations are solved for each phase together witha purely advective equation. The hybrid algorithmmultiphaseEulerFoam, which couples thecharacteristics of two-fluid models and VOF, is used to conduct simulations that are performedwith the aid of the commercial OpenFOAM software. The experiments by Govanet al.(1991)serve as a basis for creating the problem geometry and for introducing the initial and boundaryconditions in the program. Four different meshes are simulated to check the influence of themesh refinement on the numerical solution. It is found that a 15264-volume mesh is not thinenough to capture all the flow effects. At the other extreme, a finer mesh with 186560 volumes isable to detect a good interaction between the phases and to describe the flow in detail. However,this mesh is not the one that presents the best results when compared with the experimental data,because of its aspect ratio is worse than that of a mesh with 48760 volumes. The results for thevoid fraction, the pressure gradient, and the dimensionless gas superficial velocity in annularand churn flows, as well as in the transition region between them are presented, together withthe 98% air isosurfaces. In general, the relative errors found for churn flows are much smallerthan those found for annular flows and for the transition point. This occurs because the velocitydifference between the phases are smaller, therefore reducing numerical diffusion.